DAMPAK KEBIJAKAN PEMEKARAN WILAYAH TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT (Suatu Studi Di Kecamatan Gemeh Kabupaten Kepulauan Talaud) - TEGI, SYLFIA EVA; Rorong, Arie Junus (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT: To maximize the benefits of decentralization in accordance with the mandate of the Act. No. 32 of 2004 so the arrangement of the New Autonomous Region became one of the important issues that are still focusing of the Government. PP. 129 of 2000 about the Formation Requirements and Criteria for Expansion, Elimination, and Regional Merger later replaced by Regulation 78 of 2007 about Procedures for the Establishment, Abolition, and Region Merging.The efforts regional division is seen as a breakthrough to accelerate development through improving the quality of and easy access to the public service for the people. Considering the regional autonomy objective is to improve the welfare of the community, get closer to public services, and strengthen regional competitiveness. This research is intended to answer the question about what is extending impact of division policy on the social economic conditions of the society in sub district Gemehof Talaud islands.This research used a descriptive-Evaluative, with a quantitative approach. Informants in this research are 15 people that were taken by proportion 5 villages: 1 rural village is in the center of town, each village in north, south, east, and west. Instrument this research is using data collection with interview. Analyze the data with quantitative analysis.The results showed: 1) Impact of the policy of regional expansion program, 2) implementation of the policy of regional expansion program. Based on the this research results conclusion that: division policy districts Talaud islands in the form of implementation programs for infrastructure development, community empowerment and community service, especially in the sub district Gemeh of Talaud islands.Based on the results of this research, the conclusion are: 1). To improve the social economic conditions of rural communities, particularly in Sub district Gemeh, it would require concerted effort of the government together with other stakeholders to work together to improve the development of rural community infrastructure, empowering people and providing excellent service to community.2) considering the division policy had a positive effect and significantly to the improvement of social economic conditions of the people, then the government needs to deal with programs that touch directly to the community that needs as an integral part of regional divisions implemented destination itself.Keywords: Impact of Regional Expansion Policy